Pengembangan dan Implementsi Strategi Pemasaran Inovatif untuk Produk Rengginang Mini dalam Industri Makanan Ringan Metode Analisis SWOT dan Marketing MIX - Taufiqurrahman, Muhammad; Hidayat, Hidayat; Negoro, Yanuar Pandu (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Mini rengginang is a traditional Indonesian food which has been innovated into a snack and can be consumed by all groups, both young and old. This research aims to identify and implement innovative marketing strategies to increase market penetration of mini rengginang products in the snack food industry. The SWOT evaluation method is used to analyze the strengths, weaknesses, opportunities and threats associated with a product in a competitive market. Meanwhile, the application of the marketing mix aims to optimize product, price, promotion and distribution elements in order to achieve the specified marketing objectives. By integrating these two methods, this research seeks to provide a comprehensive view of how to address market challenges, identify competitive advantages, and adapt marketing strategies to gain a competitive edge in the ever-evolving snack food industry.